Laplacian Integral of Particular Steiner System - Alfi Yusrotis Zakiyyah (Engineering, MAthematics and Computer Science (EMACS) Journal, 2021)
The notion of a hypergraph is motivated by a graph. In graph, every edge contains of two vertices. However, a hypergraph edges contains more than two vertices. In this article use hyperedge to mention edge of hypergraph. A finite projective plane of order n, denoted by , is a linear intersecting hypergraph. In this research finite projective plane order is Laplacian integral.